Tolerancyjność i fanatyzm szlachty katolickiej w Rzeczypospolitej u progu Oświecenia - Głowacki, Jerzy Józef (Acta Universitatis Lodziensis. Folia Historica, 2014)
The enemies of the Confederates of Bar called them „fanatics” because of their struggle towards restoring the privileges of the Catholic faith. The confederates, as well as the public who shared their sentiments, sometimes accepted this label, accusing of religious indifference those of the nobility who did not cooperate with them. Regardless, they had quite a well-specified idea of the order among Christian denominations, the implementation of which would have realized their idea of religious tolerance. According to it, the Polish-Lithuanian Commonwealth should have preserved the privileged position of the Catholic faith, enabling, however, the people of other religions or denominations to practice their religion in private. It seemed to them of utmost importance to deny non-Catholics the right to hold office in the institutions of state in order to make the state unanimous and free from the influence of non-Catholic courts.